The Upward Pricing Pressure Test and the Sensitivity of the Diversion Ratio - Lydia Cheung (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2014)
The diversion ratio is a key ingredient to the calculation of the Upward Pricing Pressure (UPP) test, which is a new shortcut for screening mergers. It measures the degree of substitutability between the merging goods, which affects the potential for price increase post-merger. There is currently little existing research on how the diversion ratio is to be estimated (unlike its cousin, the cross-price elasticity). This paper explores one of the methods to estimate diversion ratios, which is through the estimation of a demand system. Specifically, this paper shows that the estimated value of the diversion ratio is, in fact, little affected by one of the most contentious decisions in merger analysis: the definition of the market boundary.
Keywords: 330; Upward pricing pressure; mergers